Comprehensive pharmacy review / edited by Leon Shargel [and 7 others] - Shargel, Leon; Mutnick, Alan H.; Souney, Paul F.; Kosegarten, David C.; Jambhekar, Sunil; LaSala, Edward F.; Pisano, Douglas J.; Swanson, Larry N. (Philadelphia : Harwal Publishing, 1993)
The profession of pharmacy has changed significantly during the last 3 decades. Pharmacy has evolved from the practice of preparing, preserving, compounding, and dispensing drugs to a patient-oriented practice, in which the pharmacists not only must understand the biologic and chemical nature of drugs but also must be knowledgeable health professional.
Pharmaceutics and Biopharmaceutics -- Medicinal Chemistry and Pharmacology -- Pharmacy Practice -- Clinical Pharmacy and Therapeutics
Includes index.
Keywords: PHARMACY -- EXAMINATIONS, QUESTIONS, ETC; PHARMACY -- OUTLINES, SYLABI, ETC